2020
DOI: 10.1111/aas.13548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anaesthesia‐induced hypotension and phenylephrine on plasma volume expansion by hydroxyethyl starch: A randomised controlled study

Abstract: Background Changes in blood haemoglobin concentration indicate plasma volume expansion following hydroxyethyl starch (HES) infusion, but may be affected by vascular tone and HES‐induced shedding of the endothelial surface layer (ESL). We hypothesised that anaesthesia‐induced hypotension enhances changes in plasma volume as assessed by blood haemoglobin concentration (ΔPVHb, %) following HES infusion. Methods Fifty‐two patients undergoing abdominal surgery were randomised to receive a continuous infusion of sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In vitro Cheung-Flynn et al (2019) [30] Balanced crystalloid Harmful NS Animal Byrne et al (2018) [18] -Harmful NS Animal Torres et al (2017) [31] LR, Albumin, FFP Harmful Balanced crystalloid Animal Ergin et al (2020) [34] NS Beneficial Balanced crystalloid Animal Guerci et al (2019) [35] NS Harmful HES Animal Zhao et al (2020) [40] -Beneficial HES, albumin Clinical Li et al (2020) [41] -May be beneficial HES Clinical Kaneko et al (2020) [42] -Uncertain HES Animal Smart et al (2018) [43] FWB Beneficial Gelatin Animal Smart et al (2018) [43] FWB Harmful Isotonic crystalloids Animal Smart et al (2018) [43] FWB Harmful Gelatin, dextran -Smart and Hughes (2021) [44] -Uncertain HES Animal Wong et al (2016) [49] -Harmful Albumin Animal Wong et al (2016) [49] HES Beneficial 20% Albumin Animal Damiani et al (2016) [52] 4% Albumin More beneficial NS, balanced crystalloid Animal Torres et al (2017) [31] FFP, Albumin Harmful 5% Albumin, HES Clinical Suzuki and Koyama (2020) [53] -Beneficial Albumin Clinical Piotti et al (2021) [54] -Beneficial Albumin Clinical Hariri et al (2018) [55] -Beneficial Albumin Animal, In vitro Pati et al (2016) [57] FFP Little effect Albumin Clinical Yanase et al (2021) [58] -No effect FFP Animal Nikolian et al (2017) [60] NS Beneficial FFP Animal, In vitro Wu et al (2017) [17] -Beneficial LR plus FFP Animal Vigiola et al (2019) [62] LR, LR plus albumin Beneficial FFP Clinical Straat et al (2015) [63] -Beneficial Plasma Clinical Wei et al (2018) [64] Balanced crystalloids Uncompleted OctaplasLG Clinical Stensballe et al (2018) [65] FFP More beneficial FFP Animal Nelson et al (2016) [66] Albumin, RA No difference FFP: Fresh frozen plasma; FWB: Fresh whole blood; HES: Hydroxyethyl starch; LR: Lactated Ringer solution; NS: Normal saline; OctaplasLG: Solvent-/ detergent-treated pooled plasma; RA: Ringer acetate; -: Not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro Cheung-Flynn et al (2019) [30] Balanced crystalloid Harmful NS Animal Byrne et al (2018) [18] -Harmful NS Animal Torres et al (2017) [31] LR, Albumin, FFP Harmful Balanced crystalloid Animal Ergin et al (2020) [34] NS Beneficial Balanced crystalloid Animal Guerci et al (2019) [35] NS Harmful HES Animal Zhao et al (2020) [40] -Beneficial HES, albumin Clinical Li et al (2020) [41] -May be beneficial HES Clinical Kaneko et al (2020) [42] -Uncertain HES Animal Smart et al (2018) [43] FWB Beneficial Gelatin Animal Smart et al (2018) [43] FWB Harmful Isotonic crystalloids Animal Smart et al (2018) [43] FWB Harmful Gelatin, dextran -Smart and Hughes (2021) [44] -Uncertain HES Animal Wong et al (2016) [49] -Harmful Albumin Animal Wong et al (2016) [49] HES Beneficial 20% Albumin Animal Damiani et al (2016) [52] 4% Albumin More beneficial NS, balanced crystalloid Animal Torres et al (2017) [31] FFP, Albumin Harmful 5% Albumin, HES Clinical Suzuki and Koyama (2020) [53] -Beneficial Albumin Clinical Piotti et al (2021) [54] -Beneficial Albumin Clinical Hariri et al (2018) [55] -Beneficial Albumin Animal, In vitro Pati et al (2016) [57] FFP Little effect Albumin Clinical Yanase et al (2021) [58] -No effect FFP Animal Nikolian et al (2017) [60] NS Beneficial FFP Animal, In vitro Wu et al (2017) [17] -Beneficial LR plus FFP Animal Vigiola et al (2019) [62] LR, LR plus albumin Beneficial FFP Clinical Straat et al (2015) [63] -Beneficial Plasma Clinical Wei et al (2018) [64] Balanced crystalloids Uncompleted OctaplasLG Clinical Stensballe et al (2018) [65] FFP More beneficial FFP Animal Nelson et al (2016) [66] Albumin, RA No difference FFP: Fresh frozen plasma; FWB: Fresh whole blood; HES: Hydroxyethyl starch; LR: Lactated Ringer solution; NS: Normal saline; OctaplasLG: Solvent-/ detergent-treated pooled plasma; RA: Ringer acetate; -: Not available.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 41 ] speculated that 6% HES and albumin might protect the glycocalyx integrity in patients undergoing brain surgery, excluding the factor of fluid overload. Kaneko et al [ 42 ] also found that HES administration did not aggravate the glycocalyx degradation in patients undergoing abdominal surgery. Moreover, Smart et al [ 43 ] found that compared with fresh whole blood, fluid resuscitation with HES significantly decreased the plasma hyaluronan concentration 20 min after fluid administration in a canine model of hemorrhagic shock.…”
Section: Effects Of Different Resuscitation Fluids On the Glycocalyxmentioning
confidence: 99%
“…A study reported that 59.0% of patients who developed PIH might have hypovolemia before anesthesia induction [ 10 ]. Previous studies have indicated that inadequate volume before anesthesia induction is the primary cause of PIH and perioperative fluid therapy in surgical patients before induction reduces the incidence of PIH while promoting more stable intraoperative circulation [ 11 , 12 ]. Resting pupil size and maximum constriction velocity, as well as heart rate (HR) variability can predict PIH, but these predictive indices do not comprehensively assess preoperative blood volume status in its development [ 13 15 ].…”
Section: Inductionmentioning
confidence: 99%
“…In addition, vasoactive drugs are known to alter fluid volume kinetics ( 215 219 ). Stimulation of alpha1- adrenergic receptors (e.g., norepinephrine; phenylephrine) increases V d , Cl d , the accumulation of fluid in V t , and Cl r while stimulation of beta-1 adrenergic receptors (e.g., isoproterenol) increase V c and decrease V d , Cl d , and Cl r ( 69 , 216 , 217 , 220 ). Notably, fluid accumulation in V t is more significantly influenced by the rate of infusion (i.e., ml/kg/min) than by the infused fluid volume; higher infusion rates produce greater degrees of interstitial fluid accumulation, hemodilution, coagulation abnormalities, and organ dysfunction ( 79 , 199 , 203 , 221 , 222 ).…”
Section: Volume Kineticsmentioning
confidence: 99%